Incidence of Hodgkin's lymphoma of head and neck in Baghdad city - Ahlam H Majeed; Muna S Merza (College of Dentistry/ University of Baghdad, 2013)
Background: Hodgkin's lymphoma (HL), formerly called Hodgkin's diseases is an uncommon form of lymphoma. The incidence of Hodgkin's lymphoma shows marked heterogeneity with respect to age, gender, race, geographic area, social class and histological subtype. This study was carried out in an attempt to evaluate the incidence of Hodgkin's lymphoma of head and neck in Baghdad city. Materials and Methods: The diagnosed cases of Hodgkin's lymphoma of head and neck region in Baghdad city between (1990-1999) were collected and analyzed according to age, gender, site and the histopathological subtypes of the tumor. Results: Out of (702) cases of Hodgkin's lymphoma of ten years between (1990-1999),(362 ) of them were occurred in the head and neck region including (202) males and (160) females. The remaining (340) cases were occurred in other lymph nodes of the body. Conclusion: This study revealed that predominant histopathological subtype of Hodgkin's lymphoma is the mixed cellularity type that showed more predominance in male especially among young age groups and low incidence with advancing age.